Dukungan Keluarga Dengan Tingkat Depresi Pasien Gagal Ginjal Kronis Yang Menjalani Hemodialisa (Studi Korelasi Di Rumah Sakit Gatoel Mojokerto) - Darsini Darsini (coba, 2016)
Depression is a psychological effect that is common in patients with chronic health problems such as ESRD (End Stage Renal Disease). Depression is often associated with increased morbidity of the disease. The results of preliminary studies that the researchers did found that 85% of patients with chronic renal failure undergoing regular hemodialysis at Gatoel Hospital Mojokerto depressed. Strong support system can speed up recovery of depressive episodes. The purpose of this study to determine the relationship of family support with levels of depression chronic renal failure patients undergoing hemodialysis. The research is to the type of research corellation. The population in this study were patients with chronic renal failure undergoing hemodialysis at Gatoel Hospital Mojokerto by the number of samples taken by 30 respondents with technique thst is consecutive sampling. The results showed that the majority (90%) patients with chronic renal failure undergoing hemodialysis were depressed with the largest proportion is mild and moderate depression (40%). Judging from the absence of family support is known that most of the 53% get enaugh family support. Spearman Rank Test results of the analysis results obtained p = 0,020 < α = 0,05, so Ha is received it means there is a relationships of family support with levels of depression chronic renal failure patients undergoing hemodialysis at Gatoel Hospital Mojokerto. Family support is an important form of support system for patients who are depressed. Family support appropriate and as required improved the lives an improve quality of live. Families can always be expected to provide support so that patients can develop coping mechanism and problem solving are effective. Keywords : Family Support, Depression, GGK, Hemodialysis